2023
DOI: 10.1002/ijgo.14981
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination during pregnancy: A golden opportunity to embrace

Abstract: Immunization strategies are part of routine pregnancy care to prevent infectious diseases in the mother, the fetus, and the newborn. Maternal immunization recommendations followed the recognition of the consequences of infectious diseases in pregnancy, including vertical transmission and perinatal consequences. The recent COVID‐19 pandemic highlighted the issue of vaccination among pregnant individuals. Recommendations vary globally; however, Tdap, influenza, and, recently, COVID‐19 vaccines are routinely reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Similar studies demonstrate the immunogenicity, effectiveness, and infant protection conferred by maternal vaccination . It is, therefore, disappointing that the uptake of COVID-19 vaccination in pregnancy remains suboptimal …”
mentioning
confidence: 84%
See 4 more Smart Citations
“…Similar studies demonstrate the immunogenicity, effectiveness, and infant protection conferred by maternal vaccination . It is, therefore, disappointing that the uptake of COVID-19 vaccination in pregnancy remains suboptimal …”
mentioning
confidence: 84%
“…How then do we encourage vaccination in pregnancy, against COVID-19 infection and other pathogens that threaten the health of mothers and infants? Certainly, studies such as those reported here and others reporting the longitudinal surveillance of safety, immunogenicity, and effectiveness are critical . Strong partnerships and visible support from trusted organizations such as the World Health Organization and national and professional organizations such as the Centers for Disease Control and Prevention, American College of Obstetricians and Gynecologists, American Academy of Pediatrics, and their international counterparts are important .…”
mentioning
confidence: 90%
See 3 more Smart Citations